Critical Thinking Values in Religious Narratives: CDA of ELT Learning Materials for Young Learners - Wahyuni, Irma; Syihabuddin, Syihabuddin; Gunawan, Wawan; Darazi, Mansoor Ali (UIN Salatiga, 2024)
This study examines the use of religious narratives, specifically the story of